Percutaneous Peripheral Nerve Stimulation for the Treatment of Chronic Pain Following Amputation. Issue 7 (21st May 2019) - Cohen, Steven P; Gilmore, Christopher A; Rauck, Richard L; Lester, Denise D; Trainer, Robert J; Phan, Thomas; Kapural, Leonardo; North, James M; Crosby, Nathan D; Boggs, Joseph W
Abstract: Introduction: Chronic pain and reduced function are significant problems for Military Service members and Veterans following amputation. Peripheral nerve stimulation (PNS) is a promising therapy, but PNS systems have traditionally been limited by invasiveness and complications. Recently, a novel percutaneous PNS system was developed to reduce the risk of complications and enable delivery of stimulation without surgery. Materials and Methods: Percutaneous PNS was evaluated to determine if stimulation provides relief from residual and phantom limb pain following lower-extremity amputation. PNS leads were implanted percutaneously to deliver stimulation to the femoral and/or sciatic nerves. Patients received stimulation for up to 60 days followed by withdrawal of the leads. Results: A review of recent studies and clinical reports found that a majority of patients (18/24, 75%) reported substantial (≥50%) clinically relevant relief of chronic post-amputation pain following up to 60 days of percutaneous PNS. Reductions in pain were frequently associated with reductions in disability and pain interference. Conclusions: Percutaneous PNS can durably reduce pain, thereby enabling improvements in quality of life, function, and rehabilitation in individuals with residual or phantom limb pain following amputation. Percutaneous PNS may have additional benefit for Military Service members and Veterans with post-surgical or post-traumatic pain.